Constructing Regional Identity in English and Lithuanian Newspaper Headlines: A Comparative Discourse Analysis - Sušinskienė, Solveiga (Acta humanitarica academiae Saulensis, 2026)
This research investigates the linguistic construction of regional identity in English and Lithuanian newspaper headlines using a comparative approach that combines qualitative discourse analysis with quantitative method. The research is based on a corpus of approximately 300 headlines collected from four regional newspapers: Manchester Evening News and Liverpool Echo (United Kingdom) as well as Šiaulių kraštas ‘Šiauliai Region’ and Vakarų ekspresas ‘Western Express’ (Lithuania). The analysis focuses on structural and stylistic features characteristic of headline discourse, including ellipsis, nominalisation, metaphor, wordplay, allusion, as well as emotive and evaluative language. The findings demonstrate that headlines in both languages rely on syntactic compression to convey information efficiently, although the specific realisations differ due to typological differences between English and Lithuanian. English headlines frequently employ ellipsis through the omission of articles and auxiliary verbs, whereas Lithuanian headlines tend to favour noun-based constructions and reduced clause structures. In both corpora, regional identity is constructed through frequent references to place names, local institutions, and community actors, which contextualise the news discourse within a specific geographical and social context. The research also reveals that English headlines more often use expressive strategies, such as emotive and evaluative language, metaphorical framing, while Lithuanian headlines demonstrate a relatively more informational and community-oriented style, though they also incorporate stylistic devices. Overall, the results highlight the role of headlines as condensed yet effective discursive units that shape representations of regional reality.